The flesh of the film: The camera as a body in neo-horror mockumentary and beyond. (1st November 2019) - Surace, Bruno
AbstractThe neo-horror mockumentary, from the 1990s onwards, has been a genre in constant ascent, rejuvenating extremely codified strands. What unites these strands is undoubtedly a formal commonality since the premise of the genre is that of basing oneself on 'lucky' shots, which imitate a certain amateurism, while being also extremely corporeal. The neo-horror mockumentary treats the camera as a body in its own right, with its own potential and fragility, an actor like those it films. The body of the camera and the bodies filmed by it generate a dialectic of the flesh that makes the neo-horror mockumentary a body-based genre, irrespective of its articulations, which are examined in this essay from a semiotic perspective, which investigates the role of corporeality within the formal components of the genre, a filmographic perspective that through case studies identifies the system of variants and invariants around which the body becomes a pivot, and a philosophical perspective that frames the concept of body and its change in the imaginary within this new way of making cinema.